Reclaiming the land: belonging, landscape, and in situ displacement on the plain of Karditsa (Greece). Issue 5 (19th October 2020) - Halstead, Huw
ABSTRACT: Land reform on the Karditsa plain in the late 1960s/early 1970s greatly alleviated poverty for local farmers, but also disrupted their traditional way of life and relationship with the landscape. This in situ displacement arises not from reactionary nostalgia but from rupture to inhabitants' corporeal and sensory experience of place.